A CRITICAL ANALYSIS OF THE PREVALENCE AND NATURE OF EMPLOYEE ASSISTANCE PROGRAMMES IN THE EASTERN CAPE BUFFALO CITY MUNICIPAL AREA - Govender, Thiloshni; Terblanche, Lourie (Social Work/Maatskaplike Werk, 2009)
“Being a strong advocate of an EAP does not necessarily translate into the effective implementation and oversight of an EAP” (Burke & Sharar, 2009:7) – this could be seen as a possible reason why some EAPs are more strongly aligned to certain standards or minimum requirements, as compared to other EAPs. The rationale for the original study undertaken by one of the authors of this article was exactly to explore the way in which EAPs are designed, implemented and administered in order to benefit future programmes.